AIR QUALITY MONITORING IN FOOTWEAR INDUSTRIAL AREAS USING TAIWAN AIR QUALITY MONITORING NETWORK (TAQMN) IN TAIPEI CITY - Wahyu Ratnaningsih; Wisnu Prayogo; Mochammad Charis Hidayahtullah; Rifka Noor Azizah; Husna Muizzati Shabrina; Laili Fitria (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Footwear industry in Taiwan is a large industry that supplies about 50% of the world's shoe needs. It has a positive impact on the economy, but it is also a special concern about its environmental impact, especially on air quality in Taiwan. This study aims to investigate the air quality in the footwear industrial park in Taipei City using the Taiwan Air Quality Monitoring Network (TAQMN). This study collected data from outdoor air quality measurements in the footwear industrial park in Taipei City using the Air Quality Monitoring System (AQMS) and determined its characteristics. Data were collected for 12 days from one of the stations in Datong District by monitoring the levels of major pollutants including nitrogen dioxide (NO2), carbon monoxide (CO), ozone (O3), sulfur dioxide (SO2), PM2.5 and PM10. The results show that the air quality in footwear industries has levels of PM2.5, PM10, and NO2 that exceed the thresholds set by the WHO. This has a negative impact on respiratory health and is an urgent public health issue. Factors of activity in the footwear industry, transportation, and weather patterns have important roles that determine the air quality in this region. A deep understanding of the air quality in this region is expected to provide a basis for more effective and targeted environmental policy planning to improve air quality and people's well-being in the city of Taipei.